Majątki szlacheckie w okolicy Kcyni na przełomie XIV i XV wieku = The property of nobility nearby Kcynia in the 14th c.-15th c. - Karczewska, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The medieval property nearby Kcynia was owned by knightly families of a long tradition, which inhabited this territory for generations. They included such family names as Pałuki, Poraj, Grzymała and Leszczyc. The dominating genealogy in terms of property was the Pałuki family, particularly the line residing in the Gołanice area, with the distinguishing families from Danaborz and Szaradowo.
Keywords: genealogia; szlachta; własność; Osadnictwo; settlers; genealogy; property; Nobility